BMP4 Cooperates with Retinoic Acid to Induce the Expression of Differentiation Markers in Cultured Mouse Spermatogonia - Yongguang Yang; Yanmin Feng; Xue Feng; Shangying Liao; Xiuxia Wang; Haiyun Gan; Lixian Wang; Xiwen Lin; Chunsheng Han (Stem Cells International)
Spermatogenesis is sustained by the proliferation and differentiation of spermatogonial stem cells (SSCs). However, the molecules controlling these processes remain largely unknown. Here, we developed a simplified high concentration serum-containing system for the culture of mouse SSCs. Analysis of SSCs markers and transplantation results revealed that the cultured spermatogonia retained stem cell characteristics after long-term in vitro propagation. Using this culture system, the expression and function of bone morphogenetic protein 4 (BMP4) were explored. Immunostaining showed that BMP4 was predominantly expressed in germ cells and that its level increased as spermatogenesis progresses. BMP4 receptors BMPR1A and BMPRII were present in spermatogonia, spermatocytes, and round spermatids. Moreover, despite the mRNAs of these two genes being present in mouse Sertoli cells, only BMPRII was detected by using Western blotting assays. While exogenous BMP4 by itself did not induce the expression of Stra8 and c-Kit, two marker genes of differentiating spermatogonia, a significant cooperative effect of BMP4 and retinoic acid (RA) was observed. Moreover, pretreatment of cultured spermatogonia with the BMP4 antagonist Noggin could inhibit RA-induced expression of these two marker genes. In conclusion, BMP4 may exert autocrine effects and act cooperatively with RA to induce the differentiation of spermatogonia in vivo.